1991
DOI: 10.1161/01.atv.11.3.733
|View full text |Cite
|
Sign up to set email alerts
|

Defects in platelet adhesion and aggregate formation in uremic bleeding disorder can be attributed to factors in plasma.

Abstract: Uremia is associated with bleeding diathesis. Platelet adhesion to the subendothelium is inhibited by a factor in uremic plasma that may play a role in the disturbed hemostasis of uremic patients. In the formation of the hemostatic plug, platelet adherence is followed by stimulus-induced platelet aggregation and reinforcement by thrombin-generated fibrin. To study these processes in uremic blood, a newly developed thrombosis model was used. Perfusates anticoagulated with low-molecular-weight heparin were circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 59 publications
4
24
0
Order By: Relevance
“…The pathophysiology that underlies a bleeding tendency in patients with CRF appears to involve platelet dysfunction and an imbalance of the mediators of normal endothelial function by the accumulation of uremic substances (7,8). Consistent with this, all bleeding events in the patient reported here occurred within 24 hours before a hemodialysis session.…”
Section: Discussionsupporting
confidence: 78%
“…The pathophysiology that underlies a bleeding tendency in patients with CRF appears to involve platelet dysfunction and an imbalance of the mediators of normal endothelial function by the accumulation of uremic substances (7,8). Consistent with this, all bleeding events in the patient reported here occurred within 24 hours before a hemodialysis session.…”
Section: Discussionsupporting
confidence: 78%
“…Although it can be argued that the concentration of FF recovered from uremic plasma was significantly higher than FF isolated from an equal volume of normal plasma, the fact that FF from identical volumes of plasma were added and that FF from uremic plasma caused inhibition is noteworthy and it further supports the hypothesis that elevated levels of FF may be partly responsible for platelet dysfunction in uremic patients. Moreover, our findings also suggest that the improvement of hemostatic function observed following HD [14,18,19,27,[35][36][37] might be due, in part, to a reduction in the circulating FF levels as a result of dialysis.…”
Section: Discussionmentioning
confidence: 90%
“…Mechanisms causing platelet dysfunction in uremic patients are not fully delineated; however, both platelet abnormalities [5][6][7] as well as the presence of plasma factors that adversely affect platelets have been implicated. For example, urea [27,28], guanidinosuccinic acid [29], phenols [30], and uremic MM [31] have been incriminated as factors that may cause impaired platelet function. In an exhaustive study in search of peptidic MM, Kaplan et al [9] identified several fragments of fibrinogen in uremic serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets of patients with uremia are abnormal in many ways [1, 2, 3, 4, 5, 6]. Decreased adhesion to subendothelium [1, 2], impaired formation of thromboxane [3, 4] and abnormal aggregation response to agonists [2, 3, 4, 5, 6] have been well documented.…”
Section: Introductionmentioning
confidence: 99%